Responsible Conduct of Research: Animal Care Use and Research Ethics (African Journal of Biomedical Research, 2020)
The use of animals in research has played significant roles in improving the quality of health of humans and animals. Despite these benefits, however, animals’ use in research has been subjected to oppositions on the basis of ethics and research procedures that inflict distress and compromises the welfare of the animals used. Efforts made by the international communities through laws and policies have clearly shown that research involving experimental animals must be done under acceptable scientific and ethical rules. An ethical justification to use animals in research is that the necessity and scientific significance of the research is not only for the benefit of humans, but also for the animals whose welfare may be compromised by the research. Thus, the importance of using strategies that replace sentient animals with less sentient ones, reduce the number of animals used, refine the environment, husbandry and management of animals and provide adequate veterinary care so as to minimize pain and suffering must be ensured. Ultimately, these enhance the welfare of the animals without compromising the objectives of the research. Overall, these are major issues of ethical concern. The recommendations provided by this review on care and ethics of animals used in research are based on published results and proven high-quality scientific principles that promote the welfare of animals. Finally, these can be used to develop animal care and use programs as well as check the standards of performance of research involving experimental animals.